Analisis Struktur Biaya, Titik Impas, dan Pendapatan Usahatani Cabai Merah di Desa Trimulyo Kecamatan Tegineneng Kabupaten Pesawaran - Oktaviasari Widodo, Nurul; Haryono, Dwi; Kasymir, Eka (Politeknik Negeri Lampung, 2023)
This study aimed to analyze the cost structure, break-even point, and income level in red chilli farming in Trimulyo Village. The research method used in this study was a survey. The research location was chosen purposively with the consideration that Trimulyo Village was one of the red chili-producing centers in Tegineneng District. This study collected data in November – December 2021. The method of determining the sample used in this study was a simple random sampling method by selecting 45 red chilli farmers as respondents. The data analysis method used was cost structure analysis, break-even point, and red chilli farming income. The results were that red chilli production's cost structure was dominated by labour costs originating from outside of the family, land use costs (rent), and llabourcosts originating from within the family. The value of revenue, price, and production BEPs were lower than the revenue, price, and production of red chili farming in Trimulyo Villag, sot red chilli farming was profitable. The R/C of red chili farming was greater than 1, so it could be concluded that red chilli farming, with a focus on research locations in Trimulyo Village, was profitable and deserved to be continued.